New DJ Cart OPS - Carver Cordes::::::author:::; Trevor Boelter::::::author:::; [Nate Pontious?]::::::author:::
New DJ recruitment recording possibly featuring Nate Pontious as the "contemplative freshmen," and Trevor Boelter and Carver Cordes as the second and third voices, respectively